2022
DOI: 10.1177/22808000221078168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore size on tissue ingrowth and osteoconductivity in biodegradable Mg alloy scaffolds

Abstract: Magnesium has mechanical properties similar to those of bone and is being considered as a potential bone substitute. In the present study, two different pore sized scaffolds of the Mg alloy LAE442, coated with magnesium fluoride, were compared. The scaffolds had interconnecting pores of either 400 (p400) or 500 µm (p500). ß-TCP served as control. Ten scaffolds per time group (6, 12, 24, 36 weeks) were implanted in the trochanter major of rabbits. Histological analyses, µCT scans, and SEM/EDX were performed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…86,87 The alloy LAE442 showed improved osteoconductive properties in a previous study where 500 µm interconnecting pores were used, therefore this pore size was also chosen for the scaffolds in the present study. 21,61 The delayed ingrowth of bone tissue in the present study was also reported by Lalk et al, 20 who found non mineralized bone tissue in the center of porous AX30 cylinders after 24 weeks. However, it must also be noted that the wedge used in the present study was much larger compared to the cylindrical implants, and thus the distance for ingrowing tissue into the scaffold center was much greater.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…86,87 The alloy LAE442 showed improved osteoconductive properties in a previous study where 500 µm interconnecting pores were used, therefore this pore size was also chosen for the scaffolds in the present study. 21,61 The delayed ingrowth of bone tissue in the present study was also reported by Lalk et al, 20 who found non mineralized bone tissue in the center of porous AX30 cylinders after 24 weeks. However, it must also be noted that the wedge used in the present study was much larger compared to the cylindrical implants, and thus the distance for ingrowing tissue into the scaffold center was much greater.…”
Section: Discussionsupporting
confidence: 89%
“…The slow degradation of the magnesium alloy LAE442 was also observed on small-sized porous LAE442 cylinders which were investigated in the greater trochanter of the femur in the rabbit model. [21][22][23]60,61 When comparing the coatings in the present study, it was noticed that the wedges coated only with MgF 2 (group 1) showed an overall greater volume loss than the wedges additionally coated with CaP (group 2). This indicates that additional coatings slow down degradation and at the same time gas formation.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Following von Doernberg et al (2006) , the implantation area was divided into three ROIs at ×25 magnification using three rings (IR = inner ring, MR = medial ring, OR = outer ring), with the diameter of the OR ( Ø = 4.24 mm) corresponding to the scaffold diameter ( Figure 1F ). In each ROI, a scoring system modified according to von Doernberg et al (2006) , Kleer-Reiter et al (2021) and Augustin et al (2022) was used to assess in the initial scaffold cross section the percentage area of scaffold material, bone, granulation tissue/bone marrow and resorption zone (cell- and connective tissue-rich annular zone within the scaffold cross section) as well as the percentage of scaffold material enclosed by bone ( Table 4 ). In each ROI, a second scoring system ( Table 4 ) was used to evaluate the ingrowing tissue at cellular level (fibrous cells/tissue, adipocytes, precursor cells, vascularization/blood vessels, macrophages, foreign body cells (FBC), osteoblasts, osteoclasts, osteoid) in a field of view with fixed position at ×100 magnification.…”
Section: Methodsmentioning
confidence: 99%